Análisis y mejora de los procesos de asignación y ejecución presupuestaria de proyectos de investigación de la ESPAM MFL - Chinga Zambrano, Oscar Eduardo (2020)
Within the present Degree Project, the main aspects of the continuous improvement of organizational processes were analyzed, in search of quality and excellence, this study allowed to analyze the processes and procedures of allocation and budget execution of research projects for their improvement at Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López. Through the methodology of the analysis of added value (AVA), the current state of the intervened processes was verified, in addition to identifying the main flaws that were in the different procedures and activities studied, which did not generate value for clients and institution. The results show (AVA) indices below efficiency, allowing for a restructuring of the analyzed processes, applying corrective actions through tools such as AS-IS and for their respective validation, repeatedly applying (AVA). The restructuring of the processes gave positive results and the proposals and suggestions made to achieve the improvement of the processes under study were welcomed. Finally, it is recommended to monitor the processes in order to continuously improve them to consolidate institutional and academic excellence.